An Effort To Improve Student’s Curiosity And Achievement On Social Sciences On The Topic Of Struggle Against Coloniallism Through Think Pair Share For Fifth Graaders Sdn Margasari (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2019)
The research was motivated by the students’ low curiosity and achievement in SD Negeri Margasari 04. The research was aimed to improve the quality of learning process in social science through TPS cooperative learning model then there would be an improvement of the students’ curiosity and achievement for fift graders SDN Margasari 04 Tegal. This classroom action research consisted of 2 cycles and each cycle mentioned planning, implementing, observation and reflection. For collecting the data, the research showed the first cycle that the curiosity of students was 78% then in the second cycle improved to be 85,3%. While the learning achievement mentioned 68% in the first cycle and improved to be 82,1% in the second cycle. It could be concluded that TPS cooperative learning type could improve students’ curiosity and achievement for fifth graders SDN Margasari 04.